Integrated management of Eriophyid mite, Aceria guerreronis Keifer on coconut in Tamil Nadu, India - K. Ramaraju (International Coconut Community, 2007)
A field experiment was conducted at Vellalore from January 2002 to December 2004 to evaluate the influence of organic and inorganic nutrients and the effect of botanicals and insecticide against coconut eriophyid mite. Soil application of nutrients along with spraying of Triazophos 40 EC (5 ml/lit.), azadirachtin 1% (5 ml/lit.) and neem oil (30 ml/lit.) as first, second and third round of sprayings, respectively were evaluated. The results revealed that there was a significant reduction in mite population (65%) after two years in the Integrated Management (IM) treated trees (application of organic and inorganic nutrients, basin cultivation of sunnhemp and three rounds of spraying) followed by trees treated with Nitrogen: Phosphorus: Potash (1.3:2.0:3.5 kg/palm/year) + Farm Yard Manure 50 kg/palm/year + neem cake 5 kg /palm/year + micronutrients + three rounds of sprayings (52.8%). Similarly, there was also a significant reduction in the per cent damaged green nuts after two years. After second year, the per cent damaged nut was lowest (41.9) in the IM treated trees which was statistically on par with treatment 6 (42.9) as against control (71.8). A similar trend was also recorded after third year. IM package treated trees recorded the lowest nut damage grade of 2.8, 2.4 and 2.1 at harvest followed by IM package without sunnhemp as basin crop 3.0, 2.6 and 2.2 as against 4.3, 4.3 and 4.5 in the check after first, second and third year, respectively.